2016
DOI: 10.1053/j.gastro.2015.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Infection With Camelid Hepatitis E Virus in a Liver Transplant Recipient Who Regularly Consumes Camel Meat and Milk

Abstract: There have been increasing reports of food-borne zoonotic transmission of hepatitis E virus (HEV) genotype 3, which causes chronic infections in immunosuppressed patients. We performed phylogenetic analyses of the HEV sequence (partial and full-length) from 1 patient from the Middle East who underwent liver transplantation, and compared it with other orthohepevirus A sequences. We found the patient to be infected by camelid HEV. This patient regularly consumed camel meat and milk, therefore camelid HEV, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
416
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 457 publications
(463 citation statements)
references
References 9 publications
(3 reference statements)
7
416
0
8
Order By: Relevance
“…48 However, the incidence of camelid HEV in humans in countries with large camel populations deserves further attention. to 75%) with a median short-term mortality rate of 34% (range: 0%-100%).…”
Section: Genotypementioning
confidence: 99%
“…48 However, the incidence of camelid HEV in humans in countries with large camel populations deserves further attention. to 75%) with a median short-term mortality rate of 34% (range: 0%-100%).…”
Section: Genotypementioning
confidence: 99%
“…Viruses of gt3 and gt4 cause zoonotic infections transmitted mainly by contaminated food or transfusion of contaminated blood products 5. It has been shown that gt7 can be transmitted from infected dromedaries by undercooked flesh and milk 6. HEV infections can cause arthralgia, vomiting, weakness, loss of appetite, abdominal pain, and hepatitis with accompanied symptoms, including jaundice and itching 7.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] We have recently reported possible zoonotic HEV transmission via camelderived food products. 42 Earlier studies attempting to define subgenotypes of HEV were based mainly on analysis of subgenomic regions. Subsequent analyses of whole-genomic sequences have shown that discrete boundaries may not distinguish subgenotypes consistently.…”
Section: Demographic and Clinical Featuresmentioning
confidence: 99%